IMPLEMENTATION OF USHUL FIQH AS A LEGAL BASIS FOR SOLVING SHARIA-BASED ECONOMIC PROBLEMS - Choiriyah; Saprida; Dwi Noviani; Imamul Arifin; Mahmoud Saleh Mubarak Bin Humaid (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this study is how models of the application of Usul Fiqh are used as a basic source for solving Sharia-based economic problems. Where Usul Fiqh has always been considered an essential discipline for Muslims, it lies in its position that it can easily understand modern economic laws that are not covered by other sciences. In addition, the science of Fiqh Ushul is considered to help understand and solve problems surrounding furu'iyah or fiqhiyyah that continue to develop from time to time and from various uncertain situations and conditions. The method used in this study is qualitative, with a normative approach and analytical content. The primary source of this research is text documents related to this theme. The results of the study concluded that Ushul Fiqh is considered to be a solution to legitimize and provide support for the law regarding every economic activity in every field of the transaction (muamalah), as long as it adheres to the basic principles of law, namely not violating the text and maqhasid al-Sharia.